Population density and proximity to junior developmental teams affect the development of National Hockey League draftees - Farah, L.; Schorer, J.; Baker, J.; Wattie, N. (Scandinavian Journal of Medicine & Science in Sports, 2018)
Inconsistencies in community size effects found between and within countries1-3 suggest population size may not be an accurate predictor of athlete development, and that other proxies of early environmental characteristics are needed. Researchers have begun to explore the influence of population density and proximity to local sport clubs on athlete development in European countries; however, similar analysis remains to be conducted in Canadian ice hockey. The current study focused on National Hockey League (NHL) draftees and explored whether population density and proximity to Canadian Hockey League teams were associated with the number of draftees produced. Linear regression analyses showed a significant positive relationship between population density and the development of draftees in all provincial regions; however, a significant negative relationship between proximity to CHL teams and NHL draftee development was observed in 4 out of 6 provincial regions (British Columbia, Ontario, Quebec, and the Atlantic Provinces). Moreover, population density appeared to be a better predictor of NHL talent development than proximity to CHL teams. Future research may benefit from exploring the effects of these two variables within population size categories, as well as between different regions within provinces.